Co-addition of nano-Si and LaB6 effects on the critical current density of MgB2 superconductor - Mohd Hapipi, Nurhidayah; Chen, Soo Kien; Shaari, Abdul Halim; Awang Kechik, Mohd Mustafa; Lim, Kean Pah; Shabdin, Muhammad Kashfi; Tan, Kar Ban; Lee, Oon Jew; Miryala, Muralidhar (Elsevier, 2024)
In this work, different x wt% of nano-Si and 0.03 mol LaB6 (x = 0, 5, 10) were co-added into magnesium diboride, MgB2. For comparison, samples with the addition of x wt% of nano-Si alone (x = 0, 5, 10) were prepared. All the samples were synthesized via the in-situ reaction method. X-ray diffraction (XRD) results confirmed MgB2 as the major phase, with MgO and Mg2Si as the minor phases for all the samples. Unreacted LaB6 also appeared in the co-added samples. With the addition of nano-Si from 0 to 5 wt%, Jc at 3 T and 20 K increased from 1.1 kA/ cm2 to 2.8 kA/ cm2, indicating enhanced flux pinning in high field. However, the co-addition of LaB6 and nano-Si lowered the value of self-field and field-dependent Jc. The decrease of Jc is perhaps due to the excessive impurity of Mg2Si and LaB6 leading to a reduced supercurrent path in the samples. The Tc-onset of the pure sample was 37.5 K, and it slightly decreased with increasing levels of co-addition. The flux pinning plot showed that the samples with nano-Si addition had a greater pinning force than that of the pure one.